Sarcastic Utterances in Majelis Lucu Indonesia Podcast: Pragmatics Analysis - Aprillia, Dinda; Damanik, Sisila Fitriany (Universitas Negeri Medan, 2024)
This study aims to identify four types of sarcasm in each utterance spoken by the speakers on the YouTube Channel